Mechanical demands at the ankle joint during Saut de Chat and Temps levé jumps in classically trained ballet dancers - Perry, S. K.; Buddhadev, H. H.; Brilla, L. R.; Suprak, D. N. (Open Access Journal of Sports Medicine, 2019)
Background: During ballet, injuries to the Achilles tendon are associated with the take-off phase of various jumps. Research question: The purpose of the study was to assess differences in mechanical demand on the body, specifically at the ankle, in two single-leg jumps commonly trained in ballet: a saut de chat (SDC) and a temps levé (TL). Methods: Fifteen classically trained female dancers had 16 reflective markers placed on the lower body and each dancer performed each jump three times on a force plate. The marker position data and ground reaction forces (GRF) were captured synchronously at 250 Hz and 1000 Hz, respectively. Peak vertical GRF, mean rate of force development (RFD), peak ankle moment, and peak ankle power were determined and averaged across trials. Paired t-tests were used to determine differences between the SDC and the TL. Results: When compared to the TL, the SDC displayed significantly higher peak vertical GRF (p = 0.003), RFD (p = 0.002), and peak ankle moment and power (p < 0.001). The effect sizes for these differences were large for all variables (Cohen`s d > 0.80). Conclusion: The mechanical demand at the ankle joint is significantly greater for the SDC than the TL.